Paradigma Ekonomi berkelanjutan di Negara Berkembang Dalam Perspektif Islam - Asriadi, Ari; Harahap, Isnaini; Nawawi, Zuhrinal M. (Jurnal Ilmiah Ekonomi Islam, 2024)
This article aims to uncover the dynamics of economic development in developing countries and analyze the influencing factors, focusing on identifying opportunities and challenges in achieving sustainable development. The research method utilized Systematic Literature Review (SLR), enabling the collection, evaluation, and synthesis of diverse literature related to the economic development of developing countries from 2018 to 2023. The results indicate that this study highlights the paradigm shift in the economy from the agricultural sector to the industrial and service sectors while emphasizing significant challenges such as economic inequality, limited access to healthcare and education, and negative environmental impacts. The principles of state and sustainability in Islamic economics, which are based on justice and balance, can be a strong foundation in facing economic challenges.